Year 501 : The Conquest Continues - Chomsky, Noam (London Pluto Press, 2015)
The great work of subjugation and conquest has changed little over the years. Analyzing Haiti, Latin America, Cuba, Indonesia, and even pockets of the Third World developing in the United States. Noam Chomsky draws parallels between the genocide of colonial times and the murder and exploitation associated with modern-day imperialism.
Include Glossary, Notes, Bibliography and Index.
Keywords: United States -- Imperialism -- Diplomatic relations -- World politics